Estimating thyroid profile in women with polycystic ovarian syndrome and comparing it with healthy individuals (Panacea Journal of Medical Sciences, 2024)
Background: The Polycystic Ovarian Syndrome (PCOS) is considered as one of the most common endocrinopathies in women of reproductive age having the issues related to the hyperandrogenism and oligo-anovulation. The rate of prevalence in premenopausal women is between 6-10% worldwide and in India it is around 5-10%. Interaction of small number of key genes responsible for most of the endocrine and metabolic symptom with environmental risk factors have impact on high prevalence of PCOS.Aim: To analyse thyroid profile in women with polycystic ovarian syndrome and compare it with healthy individualsThe samples were collected from PCOS patientsdiagnosed according to Rotterdam criteria, ascertained by ultrasonography, attending the OPD in the department of Obstetrics and Gynecology, Rajarajeshwari Medical college and Hospital, Bangalore from December 2014 to May 2016. Seventy-five cases of PCOS patients in the age group of 20-40 years, andseventy-five age-matched healthy women (control) with regular menstrual cycle were selected.Results: The mean age of cases was 30.13 (SD=5.32) years and mean age of control group was 28.54 (SD=6.78) years. Further, in case group, 73.33% patients were Euthyroid, 6.66% were sub-clinical hyperthyroid, 14.66% were subclinical hypothyroid and 5.33% were clinical hypothyroid. The mean value of T3 for case group was 127.13 (SD = 51.23) and control group was 137.57 (SD = 59.49). Moreover, the mean value of T4 for case group was 8.17 (SD = 2.50) and control group was 9.45 (SD = 2.24). In case group, 12.7% Euthyroid patients, 54.5% subclinical hypothyroid and 75% clinical hypothyroid had anti-thyroid peroxidase+ (TPO+). On the other hand, in control group 7.7% Euthyroid and 66.9% subclinical hypothyroid were anti-TPO+.Conclusion: Euthyroid PCOS cases with anti TPO positive are at risk of developing hypothyroidism. Thus T3, T4 and TSH should be periodically evaluated in these subjects.